2010
DOI: 10.1037/a0022078
|View full text |Cite
|
Sign up to set email alerts
|

Mestizo spirituality: Toward an integrated approach to psychotherapy for Latina/os.

Abstract: Development of culturally syntonic models for treatment that are consistent with belief systems of ethnically diverse populations is at a beginning stage of evolution. This paper is a step toward laying a new conceptual and psychotherapeutic approach with Latina/o clients, specifically those of Mexican American and Mexican backgrounds. It is argued that a psychospiritual belief system is at the base of these populations, and that a culturally consistent framework must appropriately address theory, skills, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 64 publications
0
45
0
Order By: Relevance
“…30 The emphasis of stress as a cause of MS and the value attributed to healthy eating and stress reduction suggests that Hispanics also believe in espiritism, whereby health is defined synergistically as a continuation of mind, body, and spirit. 31,32 Valuing leisure, a healthy diet (eg, concern with fast food), and stress reduction were common comments made by many study participants, suggesting that some cultural beliefs could actually help with disease management when emphasized.…”
Section: The Risk Of Strong Emotions In Hispanic Immigrantsmentioning
confidence: 99%
“…30 The emphasis of stress as a cause of MS and the value attributed to healthy eating and stress reduction suggests that Hispanics also believe in espiritism, whereby health is defined synergistically as a continuation of mind, body, and spirit. 31,32 Valuing leisure, a healthy diet (eg, concern with fast food), and stress reduction were common comments made by many study participants, suggesting that some cultural beliefs could actually help with disease management when emphasized.…”
Section: The Risk Of Strong Emotions In Hispanic Immigrantsmentioning
confidence: 99%
“…An additional study demonstrated that a healing ceremony incorporating the life stories of participants into prayer and meditation resulted in increased mental, physical, emotional, and spiritual quality of life (Hewon, Rowold, Sichler, & Walter, 2014), suggesting that ritual and ceremony might serve to boost quality of life across many different client diagnoses. Research on spiritually oriented therapeutic practices such as ritual will likely continue to grow in coming years, especially since a call has emerged for greater integration of culturally tailored spiritual practices into psychotherapy, particularly for ethnically diverse populations (Cervantes, 2010).…”
Section: Efficacy Of Ritual In Biographical Workmentioning
confidence: 99%
“…Buddhist (Nauriyal, Drummond & Lal, 2006); Christian (Jones & Butman, 1991); Islamic (Dwairy, 2006); targeting specific religious or ethnic groups i.e. Jews (Rosmarin, Pargament, Pirutinsky & Mahoney, 2010); Mormons (Martinez et al, 2007;Lyon, 2013); Latinos (Cervantes, 2010); African-Americans (Frame & Williams, 1996;Constantine, Lewis, Conner & Sanchez, 2000); Asians (Hall, Hong, Zane & Meyer, 2011;Leong & Kalibatseva, 2011); targeting specific psychological disorders, i.e. depression (Agishtein et al, 2013;Pearce & Koenig, 2013); alcoholism and drug abuse (Hodge, 2011 b ;Lietz & Hodge, 2013); eating disorders (Kristeller & Hallett, 1999;Marsden, Karagianni & Morgan, 2007); founded on specific psychotherapeutic approaches, i.e.…”
Section: Religion Spirituality and Mental Health: An Integrative Viewmentioning
confidence: 99%